Human Resource Management Practice through the Training Needs Assessment (TNA) Approach - Edi Jusriadi (Budapest International Research and Critics University, 2022)
Human Resource Management Practice in HR management mostly done in profit organizations and rarely done by public organizations. So the purpose of this research is to identify and construct a model of human resource development through a training needs assessment approach in public organizations. The research design used descriptive qualitative, by interviewing 13 informants. The result of the study indicates that: 1) the training needs assessment (TNA) model has not worked well, 2) the potential for operational personnel is not sufficient in supporting the implementation of community service tasks, both in terms of quantity, educational qualifications, skills and abilities possessed. 3) Efforts to develop intellectual capital are quite good, with policies on basic training, special training, salaries and bonuses, promotions, and work safety guarantees, and 4) Intellectual capital development has not fully had a significant impact on improving the performance of operational personnel that can be measured at the level of case handling the achievement is only 81.84%.